Rocco Schiavone: a missed Italian rough hero - Marotti, Agostino (E|C, 2020)
In the case that we want to discuss - the Italian production series “Rocco Schiavone” -, the struggle entirely within the character between the ideal of the capable and brilliant policeman and the man instead tormented by the emergence of negative feelings such as hatred and revenge. From an analytical point of view we want to highlight how these characters, in reality, can be considered as the resultant or the "sum" of several characters, we want to emphasize the fact that they are at least dual. To put it in the words of the semiologist Algirdas J. Greimas within them it is as if they were both helpers and opponents. From the viewer's point of view, these complex and conflicting characters are particularly interesting since the viewer's process of identification with them is thus favored through the complexity of the personalities represented and the slow evolution of their inner conflicts over the course of the episodes.